PENGARUH KEPEMIMPINAN ISLAM, ETOS KERJA ISLAM TERHADAP KINERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi Pada RSU PKU Muhamadiyah Gombong) - Parmin . (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
This study aims to analyze the influence of Islamic leadership, Islamic work ethic, and organizational commitment to employee performance at PKU Muhamadiyah Hospital Gombong. This research was conducted using SPSS Version 22.0 program analysis tools. The population in this study permanent employees of PKU Muhamadiyah Gombong Hospital used the probability side method of 74 people. Data collection techniques in this study used a questionnaire. This research uses descriptive analysis and statistical methods. Statistical analysis includes validity, reliability, multicollinearity, heterocedasticity tests, normality tests, t tests, coefficient of determination, correlation analysis and path analysis. The results showed that leadership, Islamic work ethic significantly influenced organizational commitment, leadership significantly influenced performance, Islamic work ethic affected performance and organizational commitment affected performance.